Healthy Living for Elders: Food Can Affect Your Medicines - Paulina Wittkowsky (EDIS)
Food can affect the way prescription and over-the-counter medicines work. This can cause unwanted effects. When taking certain medicines, some foods should be avoided. This is document FCS 8622-ENG, is one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: March 2004.